Bolts, hexagonal head, close tolerance shank, UNJF threads, split pin & locking wire hole options, titanium alloy, various finishes. Classification: Rm 1 100-1 250 MPa (160 000-180 000 lbf/in2 ) at Ambient Temperature | +315°C. (30th September 2019) - British Standards Institution,
No abstract available